Biased attention near another's hand following joint action - Sun, Hsin-Mei; Thomas, Laura E. (Frontiers in Psychology, 2013)
Previous research has shown that attention is prioritized for the space near the hand, leading to faster detection of visual targets appearing close to one’s own hand. In the present study, we examined whether observers are also facilitated in detecting targets presented near another’s hand by having participants perform a Posner cueing task while sitting next to a friend. Across blocks, either the participant or the friend placed a hand next to one of the target locations. Our results robustly showed that participants detected targets appearing near their own hands more quickly than targets appearing away from their hands, replicating previous work demonstrating that spatial attention is prioritized near one’s own hand (Experiments 1-4). No such attentional bias effects were found for targets appearing near the friend’s hand, suggesting that spatial attention is not automatically prioritized near another’s hand (Experiments 1 and 2). However, participants were faster to detect targets near the friend’s hand following a joint action task, suggesting a shared body representation plays an influential role in biasing attention to the space near another’s hand (Experiment 4).